Probiotic in Ruminant Feed - Dicky Pamungkas; Yenny Nur Anggraeni (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
The technology development of ruminant feed is related to the effort of fulfilling the nutrient requirement for maintenance and production of rumen microbes and optimizing the protein synthesis of rumen microbes, hence improving the animal production . Probiotic is widely used in feed to avoid the negative effect of antibiotic after therapeutic treatment and to be used as growth promoter . This paper describes the concept of probiotic, selection of microbes for probiotic, the benefit, the effect and the mechanism of probiotic in ruminant . In conclusion, probiotic can improve the animal growth and increase the immunity against diseases . Key words : Probiotic, growth stimulant, ruminant